(untitled) (World Bulletin of Social Sciences, 2021)
Aesthetic education in general can be seen as "the development of a person’s creative impulses to beauty." Each student has a "creative core", but due to external and internal reasons, it develops to varying degrees and in different areas; consequently, the creative potential of the child’s personality requires constant development, "polishing", purposefulness, since upbringing in its sequence is an irreversible process and upbringing mistakes are practically not corrected